Sculpting Extreme Electromagnetic Field Enhancement in Free Space for Molecule Sensing. Issue 33 (12th July 2018) - Liu, Fanxin; Song, Boxiang; Su, Guangxu; Liang, Owen; Zhan, Peng; Wang, Han; Wu, Wei; Xie, Yahong; Wang, Zhenlin
Abstract: A strongly confined and enhanced electromagnetic (EM) field due to gap‐plasmon resonance offers a promising pathway for ultrasensitive molecular detections. However, the maximum enhanced portion of the EM field is commonly concentrated within the dielectric gap medium that is inaccessible to external substances, making it extremely challenging for achieving single‐molecular level detection sensitivity. Here, a new family of plasmonic nanostructure created through a unique process using nanoimprint lithography is introduced, which enables the precise tailoring of the gap plasmons to realize the enhanced field spilling to free space. The nanostructure features arrays of physically contacted nanofinger‐pairs with a 2 nm tetrahedral amorphous carbon (ta‐C) film as an ultrasmall dielectric gap. The high tunneling barrier offered by ta‐C film due to its low electron affinity makes an ultranarrow gap and high enhancement factor possible at the same time. Additionally, its high electric permittivity leads to field redistribution and an abrupt increase across the ta‐C/air boundary and thus extensive spill‐out of the coupled EM field from the gap region with field enhancement in free space of over 10 3 . The multitude of benefits deriving from the unique nanostructure hence allows extremely high detection sensitivity at the single‐molecular level to be realized as demonstrated through bianalyte surface‐enhanced Raman scattering measurement. Abstract : A new plasmonic nanostructure is created through a unique process using ultrathin tetrahedral amorphous carbon deposition and nanofingers collapse, which enables the precise tailoring of the gap‐plasmon modes to realize strong spill‐out of the enhanced electromagnetic field. The resulting gap‐plasmon device can achieve chemical detection at the single‐molecular level while having high areal density of hotspots in free space.